2017
DOI: 10.1016/j.jjcc.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Serial assessment of right ventricular systolic function in patients with precapillary pulmonary hypertension using simple echocardiographic parameters: A comparison with cardiac magnetic resonance imaging

Abstract: Although RVFAC, TAPSE, FTWM, and FLWM were significantly correlated to CMRI-derived-RVEF, all four echo parameters showed a low sensitivity for predicting a deterioration in CMRI-derived RVEF during follow-up. Therefore, RVFAC, TAPSE, FTWM, and FLWM are not suitable parameters for the serial assessment of RV systolic function in patients with precapillary PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
(22 reference statements)
2
21
0
1
Order By: Relevance
“…In a recent report by Spruijt et al, associations between changes in echocardiographic and CMRI indices were examined in 38 PH patients. [ 19 ] Similar to the present study, their study exhibited significant associations between CMRI-derived RVEF and four echocardiographic indices of RV function (i.e., TAPSE, %RV area change, fractional longitudinal wall motion, and transverse wall motion). However, the sensitivities of these indices in detecting a decline in CMRI-derived RVEF were low at 33% to 56% and the authors concluded that such parameters were not suitable for serial assessment of RV systolic function in precapillary PH patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a recent report by Spruijt et al, associations between changes in echocardiographic and CMRI indices were examined in 38 PH patients. [ 19 ] Similar to the present study, their study exhibited significant associations between CMRI-derived RVEF and four echocardiographic indices of RV function (i.e., TAPSE, %RV area change, fractional longitudinal wall motion, and transverse wall motion). However, the sensitivities of these indices in detecting a decline in CMRI-derived RVEF were low at 33% to 56% and the authors concluded that such parameters were not suitable for serial assessment of RV systolic function in precapillary PH patients.…”
Section: Discussionsupporting
confidence: 86%
“…[ 17 ] However, echocardiography is known to encounter a challenge in obtaining clear images, particularly in PH patients with a severely dilated right heart or comorbid advanced lung disease. [ 18 ] In addition, most previous studies were cross-sectional in nature, and only a few have examined the accuracy of serial monitoring of echocardiographic indices of RV systolic function[ 19 ]. With the remarkable progress in the treatments of PH, there is a need for the development of simple, noninvasive, and reproducible methods to assess RV function in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Right atrium (RA) area was measured in the apical four-chamber view at end-systole, by tracing the RA blood-tissue interface [15]. Tricuspid annular plane systolic excursion (TAPSE) was calculated as index of RV longitudinal systolic function by placing an M-mode cursor through the tricuspid annulus in a standard apical four-chamber window, and measuring the difference between end-diastolic and end-systolic amount of longitudinal motion of the annulus (in mm) [22,23].…”
Section: M-and B-mode Measurementsmentioning
confidence: 99%
“…However, echocardiography is operator dependent and the image quality is often inadequate, especially for the RV (7) . Therefore, evaluation of the RV ejection fraction (RVEF) through the use of cardiac magnetic resonance imaging (MRI) has emerged as the gold standard for the assessment of RV function (8) .…”
Section: Introductionmentioning
confidence: 99%